Saneamento Básico e Participação Popular: A necessidade da observância do princípio democrático na implementação das políticas públicas de saneamento básico - Oliveira, Fernando Brunno Nogueira de (Universidade Federal do Tocantins, 2024)
Basic sanitation actions must comply with the participatory democratic principle, which in turn is summarized as the effectiveness of popular participation in the decision-making process of the public power that deal with the implementation of these public policies. This study aimed to identify popular participation mechanisms appropriate to issues related to basic sanitation, including citizen legitimacy for filing popular action in case of omission by public authorities and proposing informal solutions for popular participation through simplified access to decision making. decisions. For that, a research was carried out contemplating two stages and with different areas of coverage, the first stage of the study being conducted without the use of territorial delimitation, targeting citizens from all over the country and the second part of the study directed to a Brazilian municipality with low sanitation index. Interviews were made up of 2 sections, the first dealing with the analysis of demographic variables of the interviewees and the second directed to the degree of involvement with public power and monitoring of public policies on basic sanitation. The research covered topics related to sanitation, social participation and effectiveness of public power; citizen participation in public events; exercise of the right to participate in the implementation of Public Basic Sanitation Policies; possibility and interest as a citizen to contribute with the public power in decision- making on basic sanitation; ease or difficulty of dialoguing with the government; existence of campaigns to prevent diseases resulting from lack of basic sanitation; if public hearings or other public acts are instruments that facilitate the citizen's dialogue with the public power and enable social control; whether public hearings and other public acts could be replaced by informal and less bureaucratic means (smartphone applications, questionnaires and electronic forms); the causes of non- participation of citizens with public authorities in public policies on basic sanitation; public managers' interest in solving basic sanitation problems in the short term; government efficiency and omission in the implementation of public basic sanitation policies; and knowledge about the filing of lawsuits with the aim of obliging the government to take measures to improve basic sanitation services if its omission is proven. The results pointed to a lack of sanitation in Area 2, with a large number of respondents stating that they had never participated in government acts; also pointed out that, in addition to participation being a right, the will expressed by the citizen should be taken into account by the public authorities, but citizens have limitations on the right to participate in government decision-making, which is why there must be effective means that enable public participation in the debate on public policies on basic sanitation, especially considering the various informal, quick and electronic means capable of bringing citizens closer to public power, helping them in decision- making. Finally, it is concluded that popular participation is precarious, especially when it comes to public hearings within the scope of basic sanitation actions due to the lack of disclosure, distrust in the effectiveness of these hearings, lack of knowledge and discredit in the performance of the public power, reflecting that the absence of popular participation generates an imbalance between the popular will and the decisions of the authorities, since public hearings are not binding and, although citizens are willing to participate, they find obstacles in the means offered by the public Power.